The Mitochondrial Deubiquitinase USP30 Regulates AKT/mTOR Signaling - Zhang, Ruohan; Ozgen, Serra; Luo, Hongke; Krigman, Judith; Zhao, Yutong; Xin, Gang; Sun, Nuo (Frontiers in Pharmacology, 2022)
Mitophagy is an intracellular mechanism to maintain mitochondrial health by removing dysfunctional mitochondria. The E3 ligase Parkin ubiquitinates the membrane proteins on targeted mitochondria to initiate mitophagy, whereas USP30 antagonizes Parkin-dependent mitophagy by removing ubiquitin from Parkin substrates. The AKT/mTOR signaling is a master regulator of cell proliferation, differentiation, apoptosis, and autophagy. Although mounting evidence suggests that perturbations in the AKT/mTOR signaling pathway may contribute to mitophagy regulation, the specific mechanisms between Parkin/USP30 and AKT/mTOR signaling have not been elucidated. In this study, we employ a set of genetic reagents to investigate the role of Parkin and USP30 in regulating the AKT/mTOR signaling during mitophagy. We demonstrated that, in the setting of mitochondrial stress, the AKT/mTOR signaling is regulated, at least in part, by the activity of Parkin and USP30. Parkin inhibits AKT/mTOR signaling following an in vitro mitochondrial stress, thereby promoting apoptosis. However, USP30 overexpression antagonizes the activity of Parkin to sustain AKT/mTOR activity and inhibit apoptosis. These findings provide new insights into Parkin and USP30’s role in apoptosis and suggest that inhibiting USP30 might provide a specific strategy to synergize with AKT/mTOR inhibitors in cancer treatment.